2017
DOI: 10.3390/en10010051
|View full text |Cite
|
Sign up to set email alerts
|

Energy Rebound as a Potential Threat to a Low-Carbon Future: Findings from a New Exergy-Based National-Level Rebound Approach

Abstract: 150 years ago, Stanley Jevons introduced the concept of energy rebound: that anticipated energy efficiency savings may be "taken back" by behavioural responses. This is an important issue today because, if energy rebound is significant, this would hamper the effectiveness of energy efficiency policies aimed at reducing energy use and associated carbon emissions. However, empirical studies which estimate national energy rebound are rare and, perhaps as a result, rebound is largely ignored in energy-economy mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 70 publications
1
33
0
1
Order By: Relevance
“…During this period, China's economy and energy consumption have been at a plateau and the direct energy rebound effect has always been below 100%. This is basically consistent with the findings of Brockway et al [15]. The Chinese economy developed rapidly in the period of 2001-2006 due to the reform and opening up of China (Table 7).…”
Section: Direct Energy Rebound Effectsupporting
confidence: 82%
See 1 more Smart Citation
“…During this period, China's economy and energy consumption have been at a plateau and the direct energy rebound effect has always been below 100%. This is basically consistent with the findings of Brockway et al [15]. The Chinese economy developed rapidly in the period of 2001-2006 due to the reform and opening up of China (Table 7).…”
Section: Direct Energy Rebound Effectsupporting
confidence: 82%
“…Freire [14] suggested that seven of the EU's 27member states have witnessed the direct energy rebound effect higher than 100%. Brockway et al [15] pointed out that the UK and US had a low direct energy rebound effect nationwide between 1980 and 2010. Lin and Du [16] examined the direct energy rebound effect in China and found that direct energy rebound effect lay between 30% and 40% from 1981 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also compare different countries' rebound effects and their time trends. For instance, Brockway et al [3] estimated the rebound effects of China, US, and UK, and found that China had a higher rebound effect, while UK and US presented partial rebound effects. They attributed such a gap to China's "producer-sided economy" status.…”
Section: Empirical Evidence On the Rebound Effectmentioning
confidence: 99%
“…As the world's second largest economy and the largest energy consumption country, 3 China has huge energy demand and high energy-saving pressure, which impede the country's green and sustainable development. To resolve such a problem, various policies and measures focusing on improving energy efficiency have been taken in China.…”
Section: Introductionmentioning
confidence: 99%
“…10 Considera-se aqui a análise exergética como método para otimização de processos e promoção do uso eficiente dos recursos naturais. Para mais informações ver: BRISTOW; KENNEDY, 2013;BROCKWAY et al, 2017;LEDUC;VAN KANN, 2013;RAVALDE;KEIRSTEAD, 2017;ROJAS, 2007). 11 O termo "potencialidade" é empregado de forma subjetiva e pode ser encarado de várias formas.…”
Section: Contextualização Da Pesquisaunclassified